FLORISTIC DIVERSITY OF TABUK PROVINCE, NORTH SAUDI ARABIA - K. Al-Mutairi; S. A. Al-Shami; Z. Khorshid; M. M. Moawed (Journal of Animal and Plant Sciences, 2016)
The present study was aimed to investigate the floristic diversity and phytogeographical distribution of plant species along four sites i.e. Sharma, Alqan, Al-Lwaz Mountains and Alzetah from Tabuk region, Saudi Arabia. A total of 96 species belonging to 75 genera and 38 families (34 dicots and 4 monocots) were recorded. Asteraceae had the highest contribution (12.5% of the total species) followed by Fabaceae (10.42%), Zygophyllaceae (6.25%) and Lamiaceae (5.21%). The life form spectrum of the recorded species showed the prevalence of theorphytes (37%) followed by chamaephytes (32%), geeophytes (13%), hemicryptophytes (10%) and Phanerophytes (8%). The chorological analysis of the recorded species indicated the predominance of monoregional taxa over the other elements. In the same context, the flora of Tabuk region, as reflected by the present study findings, showed that most species belonged to Saharo-Arabian (37.21%), Irano-Turanian (11.63%) and Sudanean (10.47%) elements, and that constitute almost 60% of the total number of plant species. By comparing the plant diversity among the four studied sites, the highest plant diversity was reported in Alqan and Alzetah, while the lowest was reported in Sharma. It was concluded that Tabuk region had remarkable floristic diversity, however, this natural biodiversity hot spot is probably affected by several human activities including woodcutting and development. Therefore, a conservation program should be launched to protect the natural diversity in such important plant area.
Keywords: Floristic diversity; Tabuk; Suadi Arabia; Life forms; Phytogeography